2016
DOI: 10.3390/buildings6040046
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact Assessment of a School Building in Iceland Using LCA-Including the Effect of Long Distance Transport of Materials

Abstract: Abstract:Buildings are the key components of urban areas and society as a complex system. A life cycle assessment was applied to estimate the environmental impacts of the resources applied in the building envelope, floor slabs, and interior walls of the Vaettaskóli-Engi building in Reykjavik, Iceland. The scope of this study included four modules of extraction and transportation of raw material to the manufacturing site, production of the construction materials, and transport to the building site, as described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…While the building industry generates 5 to 15% of the global GDP, the built environment is responsible for one-third of the total final energy use and half of worldwide electricity consumption, as well as one-third of global carbon emissions. According to the latest IPCC report, the energy use and related emissions from buildings can double or possibly even triple until 2050 as a result of several key trends, including growth in population, relocation to urban areas, changes in family size, rising levels of affluence, and behavioral changes (Emami et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the building industry generates 5 to 15% of the global GDP, the built environment is responsible for one-third of the total final energy use and half of worldwide electricity consumption, as well as one-third of global carbon emissions. According to the latest IPCC report, the energy use and related emissions from buildings can double or possibly even triple until 2050 as a result of several key trends, including growth in population, relocation to urban areas, changes in family size, rising levels of affluence, and behavioral changes (Emami et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, GHG emissions during the operational phase are tied to the energy efficiency of buildings and the GHG intensity of energy production. Thus, the ongoing rapid development of stationary energy systems towards higher energy efficiency levels and decarbonization leads to the increasing importance of embodied, or pre-use phase, emissions (S€ ayn€ ajoki et al, 2012;Passer et al, 2012;Emami et al, 2016). For example, S€ ayn€ ajoki et al (2012) found that embodied, or pre-use phase, emissions actually dominated life cycle emissions over a 50-year life cycle in a lowenergy residential building in Finland.…”
Section: Literature Review 21 Building Life Cycle Ghg Emissionsmentioning
confidence: 99%
“…The increase in population, consumption, and depletion of non-renewable resources has impacted the built environment [1]. These changing conditions increase the need for resource-efficient buildings that consume minimal energy, provide a suitable indoor environment, and are constructed with materials that have long-term value and less waste generation [2].…”
Section: Introductionmentioning
confidence: 99%